2019
DOI: 10.3389/fimmu.2019.00902
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Type I Interferon Response During Immunosuppressive Therapy in Rheumatoid Arthritis

Abstract: Objective: The type I interferon (IFN) response in rheumatoid arthritis (RA) has been extensively studied in relation to therapy with biological DMARDs (bDMARDs). However, the effect of conventional synthetic (cs)DMARDs and glucocorticoids (GCs) on IFN response gene (IRG) expression remains largely unknown, even though csDMARDS are used throughout all disease phases, including simultaneously with biologic therapy. This study was aimed to determine the dynamics of IFN response upon immunosuppressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…We identified RA as a risk factor for death related to COVID‐19 in a multivariable‐adjusted analysis of the UK Biobank cohort. Of clinical relevance, given implication of the type 1 interferon response in biologic therapy in RA (25), is involvement of a type 1 interferon–mediated immune response in people who die of COVID‐19 (26), including in people with mutations in regulatory genes (27). It is important that the findings presented here are replicated in larger administrative data sets (eg, the US‐based National COVID Cohort Collaborative [http://www.ncats.nih.gov/n3c] and the UK OpenSAFELY cohort) (2).…”
Section: Discussionmentioning
confidence: 99%
“…We identified RA as a risk factor for death related to COVID‐19 in a multivariable‐adjusted analysis of the UK Biobank cohort. Of clinical relevance, given implication of the type 1 interferon response in biologic therapy in RA (25), is involvement of a type 1 interferon–mediated immune response in people who die of COVID‐19 (26), including in people with mutations in regulatory genes (27). It is important that the findings presented here are replicated in larger administrative data sets (eg, the US‐based National COVID Cohort Collaborative [http://www.ncats.nih.gov/n3c] and the UK OpenSAFELY cohort) (2).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated baseline IRG expression associated with increased DAS28 6 months after treatment initiation with MTX and glucocorticoid [ 5 ] as well as MTX, intramuscular glucocorticoid, and/or hydroxychloroquine [ 11 ]. However, another study found no association to disease activity 6 months after treatment initiation with MTX, prednisolone, and/or sulfasalazine [ 38 ]. In the present study, IFNα protein positivity was not related to disease activity or remission 6 months after initiation of conventional or biologic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A parallel can be drawn with the increased risk of death from COVID-19 we observed in immunodeficiencies, in that suppression of the immune system in RA using immunosuppressive disease-modifying anti-rheumatic drugs may affect the same pathway(s) contributing to death from COVID-19. Of relevance is the implication of a type 1 interferon-mediated immune response in people who die from COVID-19 (18), including in people with mutations in regulatory genes (19) given mplication of the type 1 interferon response in therapy of RA with biologics (20).…”
Section: Discussionmentioning
confidence: 99%